A Study on Safety and Efficacy of Glued Intraocular Lens Implantation in Eyes with Inadequate Capsular Support - Gonde, Payal P.; Aghadate, Sagar (Current Innovations in Medicine and Medical Science Vol. 6, 2022)
The purpose of the research was to analyse the postoperative visual outcomes, complication rate of fibrin glue- assisted, suture-less posterior chamber (PC) intraocular lens (IOL) implantation technique in eyes with inadequate capsule support at a tertiary eye care hospital and to prevent suture related complications after surgery and surgical induced astigmatism. This was a retrospective, nonrandomized case series analyzes 50 eyes which underwent PC-IOL implantation by fibrin glue-assisted, suture-less technique. From 2017 to 2019, all patients who underwent IOL implants using the PC-IOL procedure with fibrin glue assistance were included. In this study, Mean age of distribution was 42.94 years in glued IOL implantation. Out of 50 cases, 20 had females and 30 had males. The findings of this study showed that there was significant difference in BCVA between preoperatively and postoperatively, p value for pre- operative to post-operative vision in glued intraocular lens group was <0.0001 i.e. there was definite improvement in vision in glued intraocular group. BCVA \(\ge\)6/24 was 18 (48%) in Glued IOL subjects. It is concluded that Glued IOL implantation is a feasible option in rehabilitating patients with aphakia without adequate capsular support. The technique is completely suture-less in both securing the haptic and sealing the sclera flaps and conjunctiva.